Myeloproliferative neoplasms working group consensus recommendations for diagnosis and management of primary myelofibrosis, polycythemia vera, and essential thrombocythemia - Agarwal, M. B.; Malhotra, Hemant; Chakrabarti, Prantar; Varma, Neelam; Mathews, Vikram; Bhattacharyya, Jina; Seth, Tulika; Gayathri, K.; Menon, Hari; Subramanian, P. G.; Sharma, Ajay; Bhattacharyya, Maitreyee; Mehta, Jay; Vaid, A. K.; Shah, Sandeep; Aggarwal, Shyam; Gogoi, P. K.; Nair, Reena; Agarwal, Usha; Varma, Subhash; Prasad, S. V. S. S.; Manipadam, Marie Therese (Indian Journal of Medical and Paediatric Oncology, 2015)
According to the 2008 revision of the World Health Organization (WHO) classification of myeloid malignancies, philadelphia chromosome (Ph)-negative myeloproliferative neoplasms (MPNs) include clonal, hematologic disorders such as polycythemia vera, primary myelofibrosis, and essential thrombocythemia. Recent years have witnessed major advances in the understanding of the molecular pathophysiology of these rare subgroups of chronic, myeloproliferative disorders. Identification of somatic mutations in genes associated with pathogenesis and evolution of these myeloproliferative conditions (Janus Kinase 2; myeloproliferative leukemia virus gene; calreticulin) led to substantial changes in the international guidelines for diagnosis and treatment of Ph-negative MPN during the last few years. The MPN-Working Group (MPN-WG), a panel of hematologists with expertise in MPN diagnosis and treatment from various parts of India, examined applicability of this latest clinical and scientific evidence in the context of hematology practice in India. This manuscript summarizes the consensus recommendations formulated by the MPN-WG that can be followed as a guideline for management of patients with Ph-negative MPN in the context of clinical practice in India.
Keywords: Essential thrombocythemia; myeloproliferative neoplasms; polycythemia vera; primary myelofibrosis